Pengelolaan Program Corporate Social Responsibility dalam Perspektif Governance - Saleh Al Hamid (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2020)
This article aims to reveal the role of local governments in managing Corporate Social Responsibility (CSR) in Pohuwato District, Gorontalo Province. The informant in this article is that the Regional Government of Pohuwato Regency covers the Regent, Members of the DPRD, the Social Service and Community Empowerment, and the Forestry, Mining and Energy Office. From the community element, the informant is the community living around the mining exploration area and the community receiving CSR program funding assistance. Representatives from the company are the Operational Section and Community Relations of PT. Gorontalo Sejahtera Mining (GSM). Analysis of the data used is to organize data, grouping by categories, themes and answer patterns, testing the assumptions or problems that exist against the data, looking for alternative explanations for the brick, and writing the results of research. Data collection techniques with in-depth interviews and observation. The results of this study indicate that there is a role for the government in managing Corporate Social Responsibility (CSR), namely the formation of the Corporate Social Responsibility Forum (CSR Forum) initiated by the Regent. The company in this case contributes to the budgeting through the provision of assistance to houses of worship, social assistance for poor religious leaders, assistance from the underprivileged, orphanage assistance, assistance with building materials, productive economic endeavors and assistance to Remote Indigenous Communities.